Direct Comparison of Infrared Channel Measurements by Two ABIs to Monitor Their Calibration Stability - Fangfang Yu; Xiangqian Wu; Hyelim Yoo; Hui Xu; Haifeng Qian (Remote Sensing)
This paper introduces a method of monitoring infrared channel calibration stability through direct comparison of calibrated radiances by two Advanced Baseline Imager (ABI) on two geostationary (GEO) platforms. This GEO-GEO comparison is based on radiances in the overlapping area observed by the two ABIs, pixel by pixel, at approximately the same time, location, spectrum, and viewing zenith angle. It was initially developed for GOES-17 and subsequent GOES missions to validate the ABI’s calibration around its local midnight—a subject of particular interest for instruments on three-axis stabilized geostationary satellites. With the cryocooler anomaly of the GOES-17 ABI, however, the GEO-GEO comparison became an indispensable tool to characterize GOES-17 ABI infrared (IR) channel calibration with high frequency, low uncertainty, and in near real time, providing critical feedback to root cause investigation and mitigation options. Later, the GEO-GEO comparison was applied to the GOES-18 ABI as originally intended and was proved successful. It confirms that, with few exceptions, radiometric calibration for all ABIs is stable to within 0.1 K when the radiance fluctuation is converted to the brightness temperature at 300 K.